Health actions in primary care to reduce child mortality - Camila Marques Careti; Maria Cândida de Carvalho Furtado; Janaína Costa Barreto; Jéssica Batistela Vicente; Poliana Remundini de Lima (Rev Rene)
Objective: to identify the health actions aimed at reducing child mortality in primary care in a county of SãoPaulo, Brazil. Methods: an exploratory study with a quantitative approach. 54 health professionals (nurses,doctors and community health agents) participated in this study in three health units selected. Results: mostparticipants reported to develop actions to encourage breast-feeding; of the children assisted, 59.3% had theirvaccination updated; 72.2% of doctors and nurses confirmed that the children have at least one appointmentin their first week of life. For planning in health care, 51.9% reported that sometimes there is health teamparticipation in the meetings. Conclusion: several actions correspond to those recommended by the child-care public policies. However, there are weaknesses pointing at the need to enhance the vision of the healthprofessionals for greater planning, adapting to the needs of the child population in order to reduce the deaths.